Social Dynamics of Conflict over the Construction of a House of Worship in Cilegon City: Implications for Inclusive Governance and SDG 16 - Eva Hutri Sinaga; Ahmad Sihabudin; Ail Muldi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: This study aims to analyze the social dynamics underlying the conflict over the construction of the HKBP Maranatha Church in Cilegon City, identify the social and political factors that intensified the conflict, and examine the role of local government in facilitating conflict resolution. The study also considers the relevance of inclusive governance and peaceful conflict management to Sustainable Development Goal 16. Method: This research employed a descriptive qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving representatives of local government institutions, religious organizations, community groups, and parties directly affected by the conflict. The data were analyzed thematically and validated through source triangulation and member checking. Results: The findings indicate that the conflict was shaped by prejudice, interreligious distrust, unequal access to decision-making, political intervention, and ambiguity in the implementation of government regulations. The local government performed several roles as mediator, facilitator, collaborator, controller, and monitor. However, the effectiveness of these roles was constrained by inconsistent institutional responses and unequal power relations between majority and minority religious groups. Novelty: This study integrates structural conflict, symbolic interpretation, and local governance perspectives to explain how religious symbols, power inequalities, and administrative procedures interact in conflicts over houses of worship. It demonstrates that transparent regulation, inclusive dialogue, and equitable participation are essential for strengthening peaceful institutions in accordance with SDG 16.